Local modulation of steroid action: rapid control of enzymatic activity - Charlier, Thierry D.; Cornil, Charlotte A.; Patte-Mensah, Christine; Meyer, Laurence; Mensah-Nyagan, A. Guy; Balthazart, Jacques (Frontiers in Neuroscience, 2015)
Estrogens can induce rapid, short-lived physiological and behavioral responses, in addition to their slow, but long-term, effects at the transcriptional level. To be functionally relevant, these effects should be associated with rapid modulations of estrogens concentrations. 17beta-estradiol is synthesized by the enzyme aromatase, using testosterone as a substrate, but can also be degraded into catechol-estrogens via hydroxylation by the same enzyme, leading to an increase or decrease in estrogens concentration, respectively. The first evidence that aromatase activity (AA) can be rapidly modulated came from experiments performed in Japanese quail hypothalamus homogenates. This rapid modulation is triggered by calcium-dependent phosphorylations and was confirmed in other tissues and species. The mechanisms controlling the phosphorylation status, the targeted amino acid residues and the reversibility seem to vary depending of the tissues and is discussed in this review. We currently do not know whether the phosphorylation of the same amino acid affects both aromatase and/or hydroxylase activities or whether these residues are different. These processes provide a new general mechanism by which local estrogen concentration can be rapidly altered in the brain and other tissues.